An Introduction to applied economics a time series approach - Patterson, Kerry (London Macmillan, 2000)
This book is an entry book that delivers real understanding of what is done in practice by applying the philosphy that an understanding of econometrics comes from seeing it in use.It bridges the gap between techniques and applications,enabling the reader
Keywords: Economics; Econometrics